The Contribution of Adversity Quotient to Learning Outcomes of Students in Middle School and the Counseling Services Implication - Shelly Fadhila; Mudjiran Mudjiran; Nurhizrah Gistituati (Journal of Educational and Learning Studies, 2019)
Some aspects that are thought to be factors that cause success or failure of students in obtaining good learning outcomes are the ability of students to deal with and solve problems they experience (adversity quotient). The purpose of this study was to look at the effect of adversity quotient (AQ) on student learning outcomes of students and their implications in guidance and counseling services. Based on the results of the study it was found that adversity quotient give contributed to student learning outcomes. The implications of the results of this study can be used as an analysis of the needs of students in the preparation of Guidance and Counseling service programs in schools, especially at Muhammadiyah Middle School in Padang.